Comparison of perceived family structure of mothers with a disabled boy and mothers with a boy without disabilities upon circumplex model in Tehran in 1390 - Ghasemi, saeed; Hosseini, meimanat; AlaviMajd, hamid; Manochehri, hooman; Norozi, zahra (Advances in Nursing & Midwifery, 2015)
Background and aim Family structure indicates the way in which the related components of the family are organized as a whole family. Family structure is important to the outcomes of family and has main effect on family function and relationships. Circumplex Model of Marital and Family Systems (Olson) evaluates family structures and divided them to three category balanced, middle range and unbalanced families. The aim of this study was to compare the perceived family structure of mothers with a disable boy and mothers with a boy without disabilities upon circumplex model in Tehran in 1390. Materials and methods The present study is a comparative descriptive study. Data were gathered from 100 mothers who had a boy with disability and 100 mothers who had a boy without disability .The participants were included in the study from exceptional and normal elementary governmental schools in Tehran by multi-stage cluster sampling method. Data were collected by a questionnaire, which consist of two parts, demographics variables and Family Adaptability Cohesion Evaluation Scale (FACES-III) (Olson 1986) . This questionnaire has acceptable validity and reliability. This scale position the families in three type of family structures balanced, middle range and unbalanced. Data were analyzed by SPSS 16 and descriptive and analytics methods such as t- test and chi square. Findings Most of the perceived family structured in two groups were balanced and middle-range. Mothers with disable boy perceived their family structures balance and middle range less than and perceived their family structure unbalance more than the other group. Perceived family structure in two groups were not statistical significant (p>0/05). Conclusion There weren’t relationship between presences of disable child or form of disability with mother’s perceived family structure, and mothers in two groups perceive their family structure similar to each other’s. So conclusion is that family structure isn’t affected by disability of the child. Keywords Circumplex Model of Marital and Family System, Perceived family structure, mothers, disable boy, boy without disabilities